2000
DOI: 10.1258/002367700780387732
|View full text |Cite
|
Sign up to set email alerts
|

Oral buprenorphine is anti-inflammatory and modulates the pathogenesis of streptococcal cell wall polymer-induced arthritis in the Lew/SSN rat

Abstract: This study was carried out to determine an effective regimen for pain management in streptococcal cell wall (SCW)-induced arthritis in female Lew/SSN rats. Forty weanling rats lin 2 groups) were trained to accept disks of jelly as part of their dietary regimen. At 8 weeks of age weighing 150 g, SCW arthritis was induced and sublingual buprenorphine tablets were incorporated into the jelly disks to alleviate the pain of acute arthritis, which developed 24 h post-induction. Group A rats received buprenorphine at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…For example, Hall et al showed that buprenorphine inhibits osteoclastic bone resorption in an adjuvant-induced arthritis rat model [16]. Oral administration of buprenorphine was also shown to modulate the disease pathogenesis of streptococcal cell wall polymer-induced arthritis in Lew/SSN rat [9]. Bas et al demonstrated the alleviation of mechanical hypersensitivity in buprenorphine-administered QB mice during the inflammatory and postinflammatory phases of arthritis [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hall et al showed that buprenorphine inhibits osteoclastic bone resorption in an adjuvant-induced arthritis rat model [16]. Oral administration of buprenorphine was also shown to modulate the disease pathogenesis of streptococcal cell wall polymer-induced arthritis in Lew/SSN rat [9]. Bas et al demonstrated the alleviation of mechanical hypersensitivity in buprenorphine-administered QB mice during the inflammatory and postinflammatory phases of arthritis [7].…”
Section: Discussionmentioning
confidence: 99%
“…For example, mitigation of arthritis-associated mechanical hypersensitivity was demonstrated in a study that administered buprenorphine at a dose of 0.1 mg/kg body weight [7]. Similarly, buprenorphine administrated at a high dose of 2 mg/kg in Lew/SSN rats showed anti-inflammatory effects and pathophysiological changes in a streptococcal cell wall polymer-induced arthritis [9]. Our findings clearly demonstrate that buprenorphine even at lower doses, and at a time point when there are no observed clinical symptoms, interferes in the expression of inflammatory and oxidative stress molecular markers in a murine model of CIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research in the field would suggest that the functional improvements commonly involve the use of compensatory strategies rather than recovery of the normal pattern of paw use (Whishaw et al, 1991). An additional point is that buprenorphine, which was used throughout as an analgesic, has anti-inflammatory effects (Volker et al, 2000) that may affect axonal sprouting in positive or negative ways (Yin et al, 2003; Steinmetz et al, 2005; Gensel et al, 2009; Stirling et al, 2009) and alter patterns of gene expression in the microarray studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bupenorphine can be administered subcutaneously or orally in rats and mice (Liles and Flecknell, 1992a, Volker et al, 2000, Abelson et al, 2012 and has shown to be effective in treating multiple pain conditions including neuropathic pain (Guarnieri et al, 2012). Preanaesthetic subcutaneous (SC) administration of buprenorphine, during ketamine-medetomidine injectable anaesthesia, was associated with respiratory arrest and mortality in rats (Hedenqvist et al, 2000).…”
Section: Buprenorphine Is the Most Commonly Used Rodent Analgesic Agentmentioning
confidence: 99%